Design And Construction Of Jombang District Tourism Variety Information Operation System Based On Website Fream Work Codeigniter 3 - Sufaidah, Siti; Ghoni, Idham Rizky Alfatah; Arifin, Muhyiddin Zainul (NEWTON: Networking and Information Technology, 2023)
Tourism is a prospective industry in the future that requires an efficient system for providing information about tourist destinations. Jombang Regency has tourism potential that needs to be better known by the public. To improve the development of the tourism sector there, I developed a website as a tourism information system. This system considers distance, level of visits, and ratings in choosing tourist destinations. It is hoped that this system can improve the quality of service to tourists and attract their interest in visiting.